BELAJAR DARI MASA LALU, BERSIAP UNTUK MASA DEPAN: INTEGRASI PENDIDIKAN KEBENCANAAN DALAM PEMBELAJARAN SEJARAH INDONESIA - Aditya Nugroho Widiadi (Universitas Negeri Malang, 2022)
Indonesia is a disaster-prone country. History has proven that this country has been hit by various types of natural disasters for a long time. Unfortunately, disaster mitigation efforts through disaster education seem to be still not optimally conducted in Indonesia. There are only two subjects that formally contain the content of disaster education. Meanwhile, other subjects, including Indonesian history, are not required to provide students with the content of disaster education. Even though, there are many historical events in the subject of history of Indonesia that discuss the occurrence of disasters in Indonesia. Another challenge is how to integrate disaster education in history learning. One alternative method offered by this paper is through ADIT learning model. Indonesia merupakan negara yang rawan bencana. Sejarah telah membuktikan bahwa negara ini telah dilanda berbagai jenis bencana alam sejak lama. Sayangnya, upaya mitigasi bencana melalui pendidikan kebencanaan tampaknya masih belum maksimal dilakukan di Indonesia. Hanya ada dua mata pelajaran yang secara formal memuat muatan pendidikan kebencanaan. Sedangkan mata pelajaran lain, termasuk sejarah Indonesia, tidak wajib membekali siswa dengan muatan pendidikan kebencanaan. Padahal, banyak peristiwa sejarah dalam mata kuliah sejarah Indonesia yang membahas tentang terjadinya bencana di Indonesia. Tantangan lainnya adalah bagaimana mengintegrasikan pendidikan kebencanaan dalam pembelajaran sejarah. Salah satu alternatif metode yang ditawarkan oleh makalah ini adalah melalui model pembelajaran ADIT.